Czy można stworzyć jedną semantykę dla różnych płaszczyzn języka? - Florczak, Jacek (Acta Universitatis Lodziensis. Folia Linguistica, 2002)
We distinguish different features in lexeme content which correspond to different types of features generated on various language levels. The content of a lexeme in system is limited to its inherent features implied from idealised relations of identity and opposition between words. The content of a lexeme in usage depends on extraindividual linguistic associations which are beyond pure systemic contents. The content in discourse may contain also occasional features which can be totally different from systemic or usage contents. However, this various types of lexeme features specific to different language levels still belong to one lexeme in one language. This circulation of notions: 1 language ↔ different levels and I content ↔ various features rises a question: is it possible to make one semantics for one language and for one lexeme content. In the paper we want to present different methods of lexeme features analysis specific to particular language levels and to describe a tentative to obtain one method for the analysis of all types of lexeme features on all language levels. The aim of the paper is to show serious paradoxes due to confusion of different language levels and its typical contents. It is an evidence that it is impossible to obtain a consistent universal semantics giving tools for description and analysis of lexeme contents on all language levels together.